Psychedelic-Assisted Psychotherapy: A Paradigm Shift in Psychiatric Research and Development - Schenberg, Eduardo Ekman (Frontiers in Pharmacology, 2018)
Mental disorders are rising while development of novel psychiatric medications is declining. This stall in innovation has also been linked with intense debates on the current diagnostics and explanations for mental disorders, together constituting a paradigmatic crisis. A radical innovation is psychedelic-assisted psychotherapy (PAP): professionally supervised use of ketamine, MDMA, psilocybin, LSD and ibogaine as part of elaborated psychotherapy programs. Clinical results so far have shown safety and efficacy, even for "treatment resistant" conditions, and thus deserve increasing attention from medical, psychological and psychiatric professionals. But more than novel treatments, the PAP model also has important consequences for the diagnostics and explanation axis of the psychiatric crisis, challenging the discrete nosological entities and advancing novel explanations for mental disorders and their treatment, in a model considerate of social and cultural factors, including adversities, trauma, and the therapeutic potential of some non-ordinary states of consciousness.